2018
DOI: 10.1002/bse.2193
|View full text |Cite
|
Sign up to set email alerts
|

The influence of carbon cost pass through on the link between carbon emission and corporate financial performance in the context of the European Union Emission Trading Scheme

Abstract: In this study we examine, within the context of the European Union Emission Trading Scheme, whether firms' ability to pass through carbon costs affects the link between carbon emission and corporate financial performance. Our results, controlling for the endogenous relationship between carbon emission and financial performance, and robust to a number of alternative financial performance measures, demonstrate that good carbon emission performance does not always pay off. In fact, we find that lower levels of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 82 publications
(160 reference statements)
2
32
1
Order By: Relevance
“…At the same time, they find that companies that did not have this opportunity had their returns reduced by the costs. A similar relation was found by Brouwers, Schoubben, and van Hulle (2018) who show that some companies can pass on the cost of carbon to their customers because they have no competing companies in their field and can set their own prices. According to their study, a good carbon performance (lower emissions) only leads to better financial performance for companies that are not able to pass on their carbon costs.…”
Section: Background and Related Literaturesupporting
confidence: 77%
“…At the same time, they find that companies that did not have this opportunity had their returns reduced by the costs. A similar relation was found by Brouwers, Schoubben, and van Hulle (2018) who show that some companies can pass on the cost of carbon to their customers because they have no competing companies in their field and can set their own prices. According to their study, a good carbon performance (lower emissions) only leads to better financial performance for companies that are not able to pass on their carbon costs.…”
Section: Background and Related Literaturesupporting
confidence: 77%
“…Clarkson et al (2015) evaluated the impact of EU ETS on firm market value for 2006–2009 and found that EU ETS negatively affects firm market value if free allocation is lower than produced emission, and if the firm cannot transfer compliance costs to consumers. Brouwers et al (2018) investigated the first and second phases of EU ETS implementation and confirmed the results of Clarkson et al (2015). Czerny and Letmathe (2017) analysed the relationship between the environmental and economic performance of firms under the EU ETS first and second phases and found no significant relationship between the two.…”
Section: Literature Reviewsupporting
confidence: 64%
“…Borghei et al analyzed the annual reports of Australian firms and found that the return on corporate assets increased in the year following carbon information disclosure, noting that carbon information disclosure positively affects corporate financial performance [34]. Brouwers et al stated that carbon performance and information disclosure have a positive impact on corporate financial performance in the long run [35].…”
Section: Literature Reviewmentioning
confidence: 99%